A Flow Cytometry Protocol to Estimate DNA Content in the Yellowtail Tetra Astyanax altiparanae - Xavier, Pedro L. P.; Senhorini, José A.; Pereira-Santos, Matheus; Fujimoto, Takafumi; Shimoda, Eduardo; Silva, Luciano A.; dos Santos, Silvio A.; Yasui, George S. (Frontiers in Genetics, 2017)
The production of triploid yellowtail tetra Astyanax altiparanae is a key factor to obtain permanently sterile individuals by chromosome set manipulation. Flow cytometric analysis is the main tool for confirmation of the resultant triploids individuals, but very few protocols are specific for Astyanax altiparanae species. The current study has developed a protocol to estimate DNA content in this species. Furthermore, a protocol for long-term storage of dorsal fins used for flow cytometry analysis was established. The combination of 5 solutions with 3 detergents (Nonidet P-40 Substitute, Tween 20, and Triton X-100) at 0.1%, 0.2%, and 0.4% concentration was evaluated. Using the best solution from this first experiment, the addition of trypsin (0.125%, 0.25%, and 0.5%) and sucrose (74 mM) and the effects of increased concentrations of the detergents at 0.6% and 1.2% concentration were also evaluated. After adjustment of the protocol for flow cytometry, preservation of somatic tissue or isolated nuclei was also evaluated by freezing (at -20°C) and fixation in saturated NaCl solution, acetic methanol (1:3), ethanol, and formalin at 10% for 30 or 60 days of storage at 25°C. Flow cytometry analysis in yellowtail tetra species was optimized using the following conditions: lysis solution: 9.53 mM MgCl2.7H20; 47.67 mM KCl; 15 mM Tris; 74 mM sucrose, 0.6% Triton X-100, pH 8.0; staining solution: Dulbecco's PBS with DAPI 1 µg mL-1; preservation procedure: somatic cells (dorsal fin samples) frozen at -20°C. Using this protocol, samples may be stored up to 60 days with good accuracy for flow cytometry analysis.